Radioprotective Role of Peroxiredoxin 6 - Mars G. Sharapov; Vladimir I. Novoselov; Sergey V. Gudkov (MDPI AG, 2019)
Peroxiredoxin 6 (Prdx6) is a member of an evolutionary ancient family of peroxidase enzymes with diverse functions in the cell. Prdx6 is an important enzymatic antioxidant. It reduces a wide range of peroxide substrates in the cell, thus playing a leading role in the maintenance of the redox homeostasis in mammalian cells. Beside peroxidase activity, Prdx6 has been shown to possess an activity of phospholipase A2, an enzyme playing an important role in membrane phospholipid metabolism. Moreover, Prdx6 takes part in intercellular and intracellular signal transduction due to its peroxidase and phospholipase activity, thus facilitating the initiation of regenerative processes in the cell, suppression of apoptosis, and activation of cell proliferation. Being an effective and important antioxidant enzyme, Prdx6 plays an essential role in neutralizing oxidative stress caused by various factors, including action of ionizing radiation. Endogenous Prdx6 has been shown to possess a significant radioprotective potential in cellular and animal models. Moreover, intravenous infusion of recombinant Prdx6 to animals before irradiation at lethal or sublethal doses has shown its high radioprotective effect. Exogenous Prdx6 effectively alleviates the severeness of radiation lesions, providing normalization of the functional state of radiosensitive organs and tissues, and leads to a significant elevation of the survival rate of animals. Prdx6 can be considered as a potent and promising radioprotective agent for reducing the pathological effect of ionizing radiation on mammalian organisms. The radioprotective properties and mechanisms of radioprotective action of Prdx6 are discussed in the current review.